(3GdeYhbGJ hGdeTGcd GdGLQGFjI aj GdefGaP hJCKjQgG Ydi MQcI GdJLGQI Hjf GdOhd GdYQHjIs - , (3eLehYI NHQGAs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2000)
(3GdJLGQI GdYQHjI GdHjfjI aj Xd bjGe efWbI GdJLGQI GdMQI GdYQHjI GdcHQi, GdhVY GdbGFe ddeeGQSGJ hGdGLQGAGJ YfO efGaP GdYHhQ, Gdfbd GdHQj hYdGbJg HGdfhGaj GdGLQGFjI aj GdefGaP GdMOhOjI, GdGJaGbGJ GdYQHjI hGdOhdjI dJSgjd MQcI Gdfbd GdOhdj hGdYGHQ hJfejI GdJHGOd GdJLGQj, GdfJGFL hGdJhUjGJs
(3GdedGMb U(B.408s
Keywords: (3GdJLGQI GdOhdjIs; (3GdJLGQI GdYQHjIs; (3GdYGde GdYQHjs